Accounting for the Rise of Health Spending and Longevity - Raquel Fonseca; Pierre-Carl Michaud; Arie Kapteyn; Titus Galama (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We estimate a stochastic life-cycle model of endogenous health spending, asset accumulation and retirement to investigate the causes behind the increase in health spending and longevity in the U.S. over the period 1965-2005. We estimate that technological change and the increase in the generosity of health insurance on their own may explain 36.3% of the rise in health spending (technology 31.5% and insurance 4.8%), while income explains only 4.4%. By simultaneously occurring over this period, these changes may have led to complementarity e↵ects which explain an additional 59% increase in health spending. The estimates suggest that the elasticity of health spending with respect to changes in both income and insurance is larger with co-occurring improvements in technology. Technological change, taking the form of increased health-care productivity at an annual rate of 1.7%, explains almost all of the rise in life expectancy at age 25 over this period. Welfare gains are substantial and most of the gain appears to be due to technological change (47% out of a total gain of 67%).
Keywords: 330